2020
DOI: 10.7150/ijms.42086
|View full text |Cite
|
Sign up to set email alerts
|

Adenine inhibits growth of hepatocellular carcinoma cells via AMPK-mediated S phase arrest and apoptotic cascade

Abstract: Background: Adenine exhibits potential anticancer activity against several types of malignancies. However, whether adenine has anticancer effects on hepatocellular carcinoma (HCC) cells is incompletely explored. Methods: Human HCC cell lines HepG2 and SK-Hep-1 (p53-wild type) and Hep3B (p53-deficient) were used as cell model. Cell growth and cell cycle distribution were determined using MTT assay and flow cytometric analysis, respectively. Protein expression and phosphorylation were assessed by Western blot. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Our previous studies indicated that AMPK plays an important role in the anticancer activity of adenine [ 6 , 15 ]. Thus, the involvement of AMPK in the adenine-inhibited integrin/FAK cascade was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies indicated that AMPK plays an important role in the anticancer activity of adenine [ 6 , 15 ]. Thus, the involvement of AMPK in the adenine-inhibited integrin/FAK cascade was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The integrin/FAK/Src axis is strongly associated with the transformation, progression, and metastasis of tumors [ 13 ], and the activation of the FAK/Src cascade by integrin subsequently promotes cell motility and the invasiveness of cancer cells [ 14 ]. Although adenine shows antiproliferative activity on hepatocellular carcinoma cells and chronic myelogenous leukemia cells via AMPK-mediated cascade [ 6 , 15 ], whether adenine has anti-invasion activity on CRC has not yet been investigated. In this study, we aimed to explore the inhibitory effects of adenine on the invasiveness of DLD-1 and SW480 cells, which are highly metastatic and tumorigenic CRC cells, and its underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism-of-action for purine compounds has been postulated to proceed through the activation of 5′-adenosine monophosphate-activated protein kinase (AMPK), a key cancer chemotherapeutic target. Thus, the purine analog ENERGI-F706 has been recently shown to exhibit significant AMPK-mediated anticancer activities against renal and HCC cells leading to cell cycle arrest and engagement of the apoptotic cascade [ 51 , 53 ]. Cytokinin ribosides (e.g., kinetin riboside, isopentenyladenosine and benzylaminopurine riboside), but not cytokinin, have been reported to result in significant in vitro anti-leukemic effects and the enhancement of apoptosis and its biochemical markers including reduction in intracellular ATP content, loss of mitochondrial membrane potential and generation of ROS [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…AMPK activation has also been linked with induction of cell cycle arrest and cell death (Vincent et al, 2015). Anti-tumor effects of adenine for colon (Han et al, 2017), cervical (Lai et al, 2019) and hepatic (Su et al, 2020) cancer cells are mediated from adenine-induced cell cycle arrest and AMPK activated. Therefore, the cytotoxic effect of adenine on melanoma cells shown here may be through AMPK activation of adenine in melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that adenine is cytotoxic to lymphoblast (Hershfield et al, 1977;Snyder et al, 1978) and has anti-tumor activity for colon (Han et al, 2017), cervical (Lai et al, 2019) and hepatic (Su et al, 2020) cancer cells.…”
Section: Original Articlementioning
confidence: 97%